Selection of low swelling materials for protein adsorption from white wines - Sarmento, Miguel R. (2011)
The protein adsorption capacity of different materials was evaluated to assess their potential efficacy as alternative adsorbents for the removal of proteins from wines, with the purpose of finding suitable low-swelling materials that could be used in a percolated bed. The adsorbents tested were thermally treated sodium bentonite, low-swelling adsorbing clays, ion exchange resins and other protein adsorbents (silica gel, hydroxyapatite and alumina). The materials were evaluated by analysing both the capacity to stabilize untreated white wines, according to a heat test, and by characterizing the adsorption isotherms of bovine serum albumin (BSA) in a model wine (water, ethanol and K-bitartrate). Breakthrough curves in a packed bed were determined experimentally for some materials, showing the influence of the adsorption isotherm shape. Some ionexchange resins showed a favourable behaviour and have good potential as alternative adsorbents.